Analisis Faktor-faktor yang Mempengaruhi Keputusan Nasabah Menggunakan Bank Digital Syariah pada Generasi Z: Studi Kasus Mahasiswa FAI UMSU - Liza Ayu Andini; Dody Firman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Generation Z, born between the 1990s and early 2010s, is a demographic group that has unique characteristics in terms of consumption behavior and technology adoption. Along with their increasing access to the internet and mobile devices, this generation shows great interest in technology-based financial solutions, including Islamic digital banks. So this study intends to find out the aspects that affect the determination of users to use Islamic digital banks in generation Z. Through quantitative research methods using basic information in the form of distributing questionnaires. The data used were 50 respondents who used Islamic digital banks. The data obtained were processed by SPSS 21.0 for windows. Data from the research show that: 1) The Security variable has a good and relevant impact on the determination of FAI UMSU students to use Islamic digital banks. The statement is based on t-test data with a value of 0.001 ≤ 0.05. This figure can show that Ha1 is approved, which of course if the insight has a good and relevant impact; 2) The Ease variable has a good impact and is relevant to the determination of FAI UMSU students to use Islamic digital banking. This statement is based on t-test data with a value of 0.002 ≤ 0.05. This figure can show that Ha2 is approved, which means that ease has a good impact and is relevant.